Effect of high protein intervention on royal free hospital nutrition prioritising tool scores in patients with decompensated liver cirrhosis: a randomised control trial - Shobha; Reddy, M. Madhavi; Prabhakar; Rao, Nitin (International Journal of Research in Medical Sciences, 2025)
Background: The Royal Free Hospital Nutrition Prioritising Tool (RFH-NPT) is an effective instrument for assessing the nutritional status of individuals suffering from cirrhosis, demonstrating high sensitivity and specificity in detecting malnutrition risk among patients with liver cirrhosis. Methods: 110 male patients with decompensated cirrhosis were randomized, to a standard diet and a peptide supplement. The nutrition prioritizing tool, royal free hospital nutrition prioritising tool (RFH-NPT) was used to assess the effects on anthropometrics, dietary and biochemical markers. The statistically significance were analysed at p<0.05. Results: The peptide group showed significant improvement in nutrition tool scores, malnutrition and body mass index compared with controls (0.64±1.20 vs. 4.76±1.70, p<0.00 at 95% CI). Conclusions: The RFH-NPT is a valuable tool for identifying cirrhosis patients at risk of malnutrition, thereby allowing patients to receive nutritional care to improve their nutritional status and overall clinical outcomes.